GEOECONOMIC FRAGMENTATION: LIKELIHOOD OF GLOBAL FINANCIAL RECESSION AND ANALYSIS OF BANKING RISKS IN UKRAINE - LIKHONOSOVA, Ganna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article was prepared as part of the scientific research "Accounting and financial mechanism of innovative interaction of business entities in the context of the transformation of the knowledge economy and socio-behavioral restrictions." The article provides a systematization of the concerns of leading economists and financiers regarding the probability of a global financial recession. Current high inflation, low growth rates, high debt and high levels of fragmentation have been proven to reduce the incentives for investment needed to restore growth and improve living standards for the world’s most vulnerable. Both weak demand and high borrowing costs will put pressure on global financial companies, which in turn will force multinationals to cut costs, from cutting operating costs to laying off workers, it said. The author’s vision of methodological configurations and models of innovative interaction of business entities in accordance with the conditions of global challenges is given. The types of trade restrictions and barriers to technology diffusion are characterized, as well as the nature of geo-economic fragmentation that can be felt through cross-industry restrictions, namely cross-border migration, reduced capital flows and a sharp decline in international cooperation, which will make the world even more prone to upheavals. It is emphasized that the export-oriented economies especially suffer from fragmentation. Lower-income consumers in advanced economies will lose access to cheaper imported goods. Small open market economies will suffer greatly due to their heavy reliance on open trade. Supply chain disruptions are projected to have no impact on business activity in 2023, and the cost-of-living crisis may also be nearing its peak, with most. It is proposed to carry out an effective policy in the field of providing the financial market with banking regulation instruments and attracting new investment resources with a guarantee for investors to return their own funds. Scenarios for adapting the accounting and financial mechanism of innovative interaction of business entities to global challenges have been developed.